2019
DOI: 10.15294/jpii.v8i3.18907
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Science Teachers in International Teaching Practicum: Reflection of the Experience

Abstract: International Teaching Practicum (ITP) is a platform that provides experiences and opportunities for pre-service teachers to grow both personally and professionally in the teaching profession. This study reported the outcomes of an eighth-week ITP Program in Brunei and Indonesian's schools for Malaysian undergraduate secondary pre-service teachers in four aspects; namely: (1) teaching strategy in science education; (2) communication skills and confidence in teaching science; (3) perspective in science educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…Teaching practice is another topic that needs to be explored through the research process. A teaching practice model that can accommodate teachers' skills in carrying out learning in the classroom is needed (Ahmad et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Teaching practice is another topic that needs to be explored through the research process. A teaching practice model that can accommodate teachers' skills in carrying out learning in the classroom is needed (Ahmad et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Oleh karena itu perlu diperkuat bagaimana mendidik generasi yang akan datang agar mendapat kesempatan untuk membangun perdaban yang lebih baik tanpa meninggalkan adat budaya setempat. Guru adalah sosok yang dapat mengembangkan potensi peserta didik, guru merupakan figure central yang akan menjadi tolak ukur keberhasilan pendidikan [8] oleh karena itu perlu dikembangkan kompetensi guru dalam menghadapi program merdeka belajar.…”
Section: Pendahuluanunclassified
“…Some studies identified the significance of student teachers' roles and experiences. Student teachers' educational and scientific literacy had made significant changes and enhanced communication and interpersonal skills (Ahmad et al, 2019), they incorporated relationships into a constructive learning circumstance by inspiring students' hearts and minds on the educational interactions and experiences (Pourhaji, 2020), as well as showing a positive attitude toward their reflective practices (Riyanti, 2020). Teaching practicum affected student-centered learning and improved the learning quality through the constructivist learning creation, which meant to be more flexible learning, engaged students in learning processes, and reinforced social interaction and collaboration (Anagün, 2018).…”
Section: Introductionmentioning
confidence: 99%